2017
DOI: 10.1080/00016489.2017.1318220
|View full text |Cite
|
Sign up to set email alerts
|

Clinical criteria of positional vertical nystagmus in vestibular migraine

Abstract: VM can induce characteristic form of vertical positional nystagmus and vertigo, which would be treated by medications used for controlling the VM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Previous investigators also demonstrated a high prevalence of spontaneous ictal nystagmus (70%) comparable with our study (71.3%) (29). Persistent positional nystagmus while symptomatic was found in 100% of patients in two separate studies, comparable with our findings in 97.3% of patients (30,31). Occurrence of interictal spontaneous nystagmus in earlier reports of VM range between 2–11% (14.9% in our cohort) (21,32).…”
Section: Discussionsupporting
confidence: 92%
“…Previous investigators also demonstrated a high prevalence of spontaneous ictal nystagmus (70%) comparable with our study (71.3%) (29). Persistent positional nystagmus while symptomatic was found in 100% of patients in two separate studies, comparable with our findings in 97.3% of patients (30,31). Occurrence of interictal spontaneous nystagmus in earlier reports of VM range between 2–11% (14.9% in our cohort) (21,32).…”
Section: Discussionsupporting
confidence: 92%
“…During VM episodes, most patients have a central spontaneous or positional nystagmus [48,49]. The nystagmus has no latency period, is usually persistent and non-fatigable, and is markedly reduced by visual fixation [50,51]. In addition, imbalance is a regular finding during acute attacks, including a positive Romberg test and gait ataxia [17,49].…”
Section: Neuro-otological Examinationmentioning
confidence: 99%
“…The relationships among BPPV, migraine, and stress or anxiety are complicated . Both BPPV and VM may present with positional nystagmus during positional testing, but positional nystagmus in VM patients is up‐ or down‐beating without latency or fatigue . In addition, BPPV is frequently associated with comorbidities such as migraine .…”
Section: Discussionmentioning
confidence: 99%
“…28 Both BPPV and VM may present with positional nystagmus during positional testing, but positional nystagmus in VM patients is up-or down-beating without latency or fatigue. 29 In addition, BPPV is frequently associated with comorbidities such as migraine. 30,31 In our patient, dizziness was triggered by stress and anxiety, provoked, for example, by school examinations, suggesting a possible comorbidity of BPPV and migraine.…”
Section: Discussionmentioning
confidence: 99%